2011
DOI: 10.1128/jvi.00220-11
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Isolates of Trichomonas vaginalis Concurrently Infected by Strains of Up to Four Trichomonasvirus Species (Family Totiviridae)

Abstract: Trichomonas vaginalis, which causes the most common nonviral sexually transmitted disease worldwide, is itself commonly infected by nonsegmented double-stranded RNA (dsRNA) viruses from the genus Trichomonasvirus, family Totiviridae. To date, cDNA sequences of one or more strains of each of three trichomonasvirus species have been reported, and gel electrophoresis showing several different dsRNA molecules obtained from a few T. vaginalis isolates has suggested that more than one virus strain might concurrently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 49 publications
7
80
0
3
Order By: Relevance
“…The identity values among PMeV isolates are close to those observed in a similar study comprising RdRp from nineteen isolates belonging to four possible species of Trichomonas vaginalis virus (TvV-1 to 4), which determined that the level of identity ranged from 82 to 94%, depending on the virus specie (Goodman et al, 2011). In another study with TvV isolates from Cuba, it was found that the conservation in the aa sequence of RdRp was of 81 to 85% (Fraga et al, 2012).…”
supporting
confidence: 58%
“…The identity values among PMeV isolates are close to those observed in a similar study comprising RdRp from nineteen isolates belonging to four possible species of Trichomonas vaginalis virus (TvV-1 to 4), which determined that the level of identity ranged from 82 to 94%, depending on the virus specie (Goodman et al, 2011). In another study with TvV isolates from Cuba, it was found that the conservation in the aa sequence of RdRp was of 81 to 85% (Fraga et al, 2012).…”
supporting
confidence: 58%
“…Up to four different species of viruses (TVVs) can infect T. vaginalis simultaneously [17], and this raises questions regarding competition, recombination and packaging of virus particles that still need to be investigated. TVVs induce phenotypic plasticity in the surface immunogen P270, which could lead to evasion of the mammalian immune response (reviewed in [18]).…”
Section: Viruses Of Other Parasitic Unicellular Eukaryotesmentioning
confidence: 99%
“…Also, T. vaginalis carries viruses and other parasites, such as mycoplasma and gardenella, causing chronic mucosal damage and an inflammatory reaction which gives rise to severe consequences in reproductive outcomes [21][22][23][24]. Goodman et al [24] reported the presence of a Totiviridae viral family, which is a virus with a doubled stranded RNA that concurrently, is infecting the T. vaginalis parasite [24][25][26]. Infection of T. vaginalis by such a virus increases severely the immunological genesis of trichomona virulent factors by changes in its genome organization, protein coding, and replication signals.…”
Section: Transmission Of T Vaginalis Infection Is Exclusively Throughmentioning
confidence: 99%
“…Infection of T. vaginalis by such a virus increases severely the immunological genesis of trichomona virulent factors by changes in its genome organization, protein coding, and replication signals. Trichomona virus increases the recurrence of the parasite infection and resistance to the metronidazole treatment [7,24,[27][28][29]. Several reports punctuate the serious and detrimental outcome of trichomoniasis in pregnancy but exists a gap of knowledge in the correlation of T. vaginalis infection with unexplained infertility in humans.…”
Section: Transmission Of T Vaginalis Infection Is Exclusively Throughmentioning
confidence: 99%